2017
DOI: 10.1093/trstmh/try013
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping of Giardia duodenalis in vegetables cultivated with organic and chemical fertilizer from street markets and community vegetable gardens in a region of Southern Brazil

Abstract: The molecular technique revealed genotypes with zoonotic potential, evidencing the importance of investigating commercialized vegetables that are consumed raw and establishing a more rigid quality control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…The PCR amplification and sequencing of specific G. duodenalis genes recovered from contaminated food are also commonly used for the confirmatory detection of this parasite (e.g. [28,39,44]).…”
Section: Giardia Duodenalis Contaminationmentioning
confidence: 99%
See 2 more Smart Citations
“…The PCR amplification and sequencing of specific G. duodenalis genes recovered from contaminated food are also commonly used for the confirmatory detection of this parasite (e.g. [28,39,44]).…”
Section: Giardia Duodenalis Contaminationmentioning
confidence: 99%
“…The contamination of vegetables and fruits with G. duodenalis cysts has been reported in many countries (Table 2), and the average prevalence is estimated as 4.8% (276/5739; 95% CI: 4.2-5.4%). In contaminated vegetable and fruit samples, G. duodenalis zoonotic assemblages A and B were commonly detected [23,28,39,44,45].…”
Section: Giardia Duodenalis Contaminationmentioning
confidence: 99%
See 1 more Smart Citation
“…(21,28,40,43,47,48,49,50,51,52) The most used target in PCR-RFLP was gdh, and sometimes appeared combined with the target βg. (21,43,47,48,49,50,51,52) Only one study used only the βg target for genotyping in PCR-RFLP. (28) In these studies, PCR-RFLP showed a satisfactory result in identifying the assemblages circulating, with the exception of just one study where PCR-RFLP data obtained by sequencing did not determine the assemblage of isolates from samples of humans, dogs and vegetables.…”
Section: Genotyping Strategies Of G Duodenalis In Brazilmentioning
confidence: 99%
“…Paraná Human A (48,49,77) B (48,49,77) Dog B (49) C (49) D (49) Vegetable A (51,62) B (49,51) E (41,51) Water E (41) Soil E (41) Santa Catarina Human A (52) B (52) Dog A ( 52) B ( 52) C (52) Nonhuman primates A (31) Uninformed Jaguar A (32) Monkey B (32) Chinchilla B (32) Ostriches B (32) ents a single study (41) (Table II) (Fig. 3).…”
Section: Isolate Origin Assemblagementioning
confidence: 99%